2015
DOI: 10.1093/mmy/myv074
|View full text |Cite
|
Sign up to set email alerts
|

Human Invariant Natural Killer T cells possess immune-modulating functions duringAspergillusinfection

Abstract: Aspergillus fumigatus is the most common cause for invasive fungal infections, a disease associated with high mortality in immune-compromised patients. CD1d-restricted invariant natural killer T (iNKT) cells compose a small subset of T cells known to impact the immune response toward various infectious pathogens. To investigate the role of human iNKT cells during A. fumigatus infection, we studied their activation as determined by CD69 expression and cytokine production in response to distinct fungal morphotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Furthermore, CD1d-deficient mice poorly control infections with Aspergillus fumigatus ( Cohen et al., 2011 ) reflecting the need for NKT cells in the control of fungal infections. In addition, human NKT cells exhibit immunomodulatory effects following exposure to Aspergillus spp ( Beitzen-Heineke et al., 2016 ).…”
Section: Nkt Cell Antigensmentioning
confidence: 99%
“…Furthermore, CD1d-deficient mice poorly control infections with Aspergillus fumigatus ( Cohen et al., 2011 ) reflecting the need for NKT cells in the control of fungal infections. In addition, human NKT cells exhibit immunomodulatory effects following exposure to Aspergillus spp ( Beitzen-Heineke et al., 2016 ).…”
Section: Nkt Cell Antigensmentioning
confidence: 99%
“…Mechanistically, this report demonstrated that Dectin-1-and MyD88-dependent responses promoted IL-12 production by DCs that drove NKT cells to secrete interferon (IFN)-γ. Building upon this observation, human NKT cells were examined for their response to distinct fungal morphotypes and DCs [24] . It was shown that CD1d+ CD1c+ myeloid DCs were the most potent activator of NKT cells.…”
Section: Macrophages Inflammatory Monocytes Eosinophils and Naturamentioning
confidence: 99%
“…Alveolar macrophages, neutrophils, and peripheral blood monocytes are the first line of phagocytic host anti- Aspergillus defences to inhaled conidia and hyphae [ 4 , 14 ]. Cytokine-mediated recruitment of natural killer effector cells is necessary for effective host defence against Aspergillus infection [ 15 ]. Additionally, a number of membrane-bound and soluble pathogen-recognition receptors (PRRs) that identify fungal motifs including toll-like receptors (TLRs), dectin-1, surfactant proteins A and D, mannose-binding lectin (MBL), and pentraxin-3 are important triggers of innate immune response leading to complement activation, phagocytosis, and killing of ingested fungi [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%